Production of Biosurfactants by Ascomycetes - Michele Alves Sanches; Isabella Galvão Luzeiro; Ana Cláudia Alves Cortez; Érica Simplício de Souza; Patrícia Melchionna Albuquerque; Harish Kumar Chopra; João Vicente Braga de Souza (International Journal of Microbiology)
Surfactants are utilized to reduce surface tension in aqueous and nonaqueous systems. Currently, most synthetic surfactants are derived from petroleum. However, these surfactants are usually highly toxic and are poorly degraded by microorganisms. To overcome these problems associated with synthetic surfactants, the production of microbial surfactants (called biosurfactants) has been studied in recent years. Most studies investigating the production of biosurfactants have been associated mainly with bacteria and yeasts; however, there is emerging evidence that those derived from fungi are promising. The filamentous fungi ascomycetes have been studied for the production of biosurfactants from renewable substrates. However, the yield of biosurfactants by ascomycetes depends on several factors, such as the species, nutritional sources, and environmental conditions. In this review, we explored the production, chemical characterization, and application of biosurfactants by ascomycetes.